Accounting, the basis for business decisions - Meigs, Walter B.; Meigs, Robert F. (New York : McGraw Hill Education, 1984)
A new edition provides authors with an opportunity to add new material, to condense the coverage of topics that have declined in relative importance, to reorganize portions of the book to improve instructional efficiency, and to refine and polish the treatment of basic subject matter. We have tried to do all these things in this sixth edition. The environment of accounting is changing fast, and these environmental changes, such as continued inflation and the critical financial problems of many cities, affect the goals and the content of an introductory text in accounting. In order to function intelligently as a citizen as well as in a business of any size or type, every individual needs more than ever before a clear understanding of basic accounting concepts. In this sixth edition, we have tried to reflect the impact of inflation on accounting measurements and to suggest the direction of needed changes in accounting concepts and methods. The importance of adequate disclosure in the system of financial reporting is stressed, and attention is drawn to the need for improved accounting controls in all sectors of society.
1. Accounting: The Language of Business -- 2. Recording Changes in Financial Position -- 3. Measuring Business Income -- 4. Completion of the Accounting Cycle -- 5. Accounting for Purchases and Sales of Merchandise -- 6. Internal Control -- 7. Accounting Systems: Manual and EDP -- 8. The Control of Cash Transactions -- 9. Receivables and Payables -- 10. Inventories -- 11. Plant and Equipment: Depreciation -- 12. Plant and Equipment, Natural Resources, and Intangibles -- 13. Payroll Accounting -- 14. Accounting Principles and Concepts: Effects of Inflation -- 15. Partnerships -- 16. Corporations: Organization and Stockholders' Equity -- 17. Corporations: Operations, Earnings Per Share, and Dividends -- 18. Corporations: Bonds Payable, Leases, and Other Liabilities.
Includes index.
Keywords: ACCOUNTING